Does a Deposit Insurance Scheme Induce Moral Hazard among Bankers? Evidence from an experiment with bankers - Gumilang Aryo Sahadewo; Bernardinus Maria Purwanto; Rimawan Pradiptyo (Gadjah Mada International Journal of Business, 2018)
The implementation of a deposit insurance scheme entails a trade off. On one hand, as shown in theoretical and empirical studies, a deposit insurance scheme reduces the likelihood of a bank run. On the other hand, a deposit insurance scheme induces moral hazard among bankers that may lead to bank failures. We rigorously test the effect of different deposit coverage limit and the implementation of a differential premium treatment on bankers’ behaviors in the deposit and credit market. We do so by designing a laboratory experiment that involves real bankers as participants. We find that the coverage limit treatments do not have any effect on deposit rate offer. Nevertheless, we find that a high deposit coverage limit induces smaller banks to have a higher share of risky projects. This is evidence of moral hazard particularly among small banks.